Adherence to Swedish national pregnancy dating guidelines and management of discrepancies between pregnancy dating methods: a survey study - Merit Kullinger; Michaela Granfors; Helle Kieler; Alkistis Skalkidou (BMC, 2019)
Abstract Background Swedish national guidelines for pregnancy dating were published in 2010. Follow-up is needed to assess adherence and to identify whether any clinical topics are not covered in the guidelines. Methods All units in Sweden that performed ultrasound-based pregnancy dating were asked to complete a web-based questionnaire comprising multiple-response questions and commentary fields. Information was collected regarding baseline information, current and previous clinical practice, and management of discrepancies between last-menstrual-period- and ultrasound-based methods for pregnancy dating. Results The response rate was 79%. Half of the units offered first-trimester ultrasound to all pregnant women. However, contrary to the guidelines, the crown-rump length was not used for ultrasound-based pregnancy dating in most units. Instead, ultrasound-based pregnancy dating was performed only if the biparietal diameter was between 21 and 55 mm. Management of discrepancies between methods for pregnancy dating varied widely. Conclusions The units reported high adherence to national guidelines, except for early pregnancy dating, for which many units followed unwritten or informal guidelines. The management of discrepancies between last-menstrual-period-based and ultrasound-based estimated day of delivery varied widely. These findings emphasize the need for regular updating of national written guidelines and efforts to improve their implementation in all units.